Sistem Informasi Pengelolaan Surat Masuk dan Surat Keluar - Endang Amalia; Carolina Anty L (CV. Multi Kreasi Media, 2023)
Letters are media in communicating and as evidence of an event. The obstacle that occurs when using letters in physical form is the management that must be good so that letters are not easily lost or damaged. The problem faced by the Cicalengka District Education Work Unit office is that there is a lot of use of paper in managing letters and writing letter management reports that must be counted one by one every month. As well as the distribution of letters has not been organized to each section. The purpose of creating an information system for managing incoming and outgoing mail at the Cicalengka District Education Work Unit is to be able to manage mail data so that it is organized and can assist officers in preparing reports. The design of Incoming and Outgoing Mail Management Information Systems uses the UML (Unified Modeling Language) method, namely with use case diagrams and activity diagrams. Based on the results of implementation and testing, the system has been able to run in accordance with the business processes contained in the Cicalengka District Education Work Unit in managing incoming and outgoing mail data. The test used is blackbox testing and interviews. Blackbox testing is testing to test system functionality carried out by the system developer. Interviews were conducted with two employees of the Cicalengka District Education Work Unit Office, the Head of Sub-division & General Affairs Manager.